Abrigo 1, Cerro El Sombrero: An Early Site in Eastern Argentina. (2nd January 2023) - Zárate, Marcelo; Flegenheimer, Nora; Mehl, Adriana
ABSTRACT: Late Pleistocene human occupations are well represented in the Tandilia Range, Argentine Pampas. Abrigo 1 is a small shelter in close relation to the main and better-known site on the hilltop of Cerro El Sombrero, with both sites including Fishtail points. The oldest levels at the shelter dated to 13, 000–12, 000 calendar years ago and yielded two Fishtail points. This paper deals with the analysis of the sedimentary context, stratigraphy, artifact distribution, and site formation processes at Abrigo 1. The sedimentary record is dominantly composed of geogenic sediments with a minor participation of anthropogenic material, mainly lithic artifacts. The geogenic input includes sediments coming from the physical and chemical weathering of the rockshelter's quartzites and windblown sediments. Pedogenesis is the prevailing site formation process. Artifact distribution, the homogeneity of the assemblage, and refitting are considered relevant to assess site integrity. The results are compared to other early cultural contexts of the immediate vicinity.